Additional notes on Ipomoea (Convolvulaceae) in Bolivia - Wood, JRI; Martinez-Ugarteche, MT; Muñoz-Rodríguez, P; Scotland, RW (Springer, 2018)
109 species of Ipomoea L. are recorded from Bolivia. This total includes six new country records and two species, I. prolifera J. R. I. Wood & Scotland and I. inaccessa J. R. I. Wood & Scotland, which are described as new, while I. jujuyensis O'Donell is excluded having been included previously in error. The little-known I. subalata Hassl. is described in full and compared with I. chondrosepala Hallier f. and other species with which it has been confused. The paper is illustrated with line drawings, photographs and distribution maps of the main species discussed.